Junk food: A preliminary analysis of ingested marine debris by hawksbill Eretmochelys imbricata and olive ridley Lepidochelys olivacea sea turtles (Testudines: Cheloniidae) from the eastern coast of the United Arab Emirates. (December 2021) - Yaghmour, Fadi; Al Bousi, Marwa; Al Naqbi, Halima; Samara, Fatin; Ghalayini, Thouraya
Abstract: For the first time, the qualitative and quantitative characteristics of marine debris ingested by six hawksbill ( Eretmochelys imbricata ) and seven olive ridley ( Lepidochelys olivacea ) sea turtles from the Gulf of Oman coast of the United Arab Emirates were investigated. The numeric and gravimetric proportions of ingested marine debris obtained from the esophagus, stomach and intestines were quantified following categories of presumed sources, Marine Strategy Framework Directive (MSFD), rigidity, color and plastic polymer types. Marine debris was observed in 28.6% of olive ridley (x̅: 2.00 items; 4.83 g) and 83.3% of hawksbill specimens (x̅: 6.00 ± 2.32 items; 0.32 ± 0.24 g). Overall, the results of this preliminary study suggest that hawksbill sea turtles were ingesting marine debris at higher frequencies and that plastics were observed to be the most predominant debris ingested. However, non-plastic rubbish, particularly metallic fishing gear (fish hooks and fish traps), were observed to present lethal hazards for both species. Graphical abstract: Unlabelled Image Highlights: Here, we examine marine debris ingestion by hawksbill and olive ridley sea turtles. Debris was detected in 83.3% of hawksbill and 28.6% of olive ridley sea turtles. Hawksbill sea turtles ingested 6.00±2.32 marine debris items weighing 0.32±0.24g Two olive ridleys each ingested 2 marine debris weighing 0.58g and 9.09g. In both species plastics were the predominant type of ingested marine debris